(untitled) (Fiep Bulletin - online, 2014)
The research of qualitative nature was developed in the fantasy world field and it had as goals: 1) To investigate the meanings of the adventure of walking for leisure in the fantasy world of the pilgrims-hikers who trekked the Caminho do sol (Path of the Sun). 2) To highlight the simbolic elements that emerge from those discourses and the images of the route of Caminho do Sol. 3) To reveal in which measure the pilgrim-hiker rescues the sacred of his own nature. Nine depositions of the pilgrim-hiker who went through Caminho do Sol were analysed, using the method of Discourse-Analysis of Eny Orlandi. The Caminho do Sol is located in the State of São Paulo, it starts in Santana do Parnaíba and finishes in Águas the São Pedro. Trekking this path is more than a walking ,it is a trekking in a leisure time: It’s to trek the way of hero/adventurer, of re-enchantment, of the reintegration body/spirit, and the union with God. The origin of the discourse of pilgrimage admits the religious trace but nowadays religion joins nature, turning to leisure/adventure/nature/spiritual well-being. The pilgrim-hiker re-enchanted himself, found feelings that were already lived by other men, during the period of enchanted world. He showed seduced and snatched by the charming of nature, living spiritual well-being, the happiness.